ANALISIS ASAS AUDI ET ALTERAM PARTEM DALAM PRAKTIK PERADILAN PERDATA DI INDONESIA - Lubis, Fauziah; Humaira, Sandrina Aika; Zahrah, Athirah; Saragih, Alvito Audryanza; Hasibuan, M. Radit Febrianda; Agustira, Nadia (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This study aims to analyze the implementation of the audi et alteram partem principle in Indonesian civil procedural law, particularly within the context of digitalized court systems. The main issue examined concerns the extent to which this principle guaranteeing each party the right to be heard before a judgment is rendered is applied in court proceedings and the obstacles that hinder its realization. As a cornerstone of procedural fairness, its relevance is increasingly challenged by the integration of e-court systems, which introduce new barriers such as unequal access to technology, limited legal literacy, and administrative constraints. Using a normative legal method with statutory, conceptual, and case-based approaches, the research draws upon legislation, court decisions, and legal doctrine. The findings reveal that although the principle is normatively acknowledged, its practical enforcement remains inconsistent. Special attention is given to verstek (default judgments), where the absence of one party raises concerns over the fairness of the process. The study underscores the need for regulatory reform, enhanced judicial capacity, and critical evaluation of electronic litigation procedures to ensure that audi et alteram partem is genuinely upheld in civil court practices.